Evaluation of superplastic characteristics of tubular materials by multi-tube bulge test - (:unkn) unknown (ELSEVIER SCIENCE BV, 2006)
In this study, the superplastic characteristics of tubular material Ti-alloy Ti-4.5Al-3V-2Fe-2Mo, commercial name SP-700, has been characterized by a new testing method Multi-tube bulge test. After the test, every tube specimen has four different bulge shapes, sized 50, 40, 30, and 20 mm, respectively. The flow stress and the strain rate were then calculated at the apex of every bulge part using membrane theory and then the relationship could be established for certain strain rate range, from a single tube specimen. Multi-tube bulge experiments were conducted under constant pressure at a superplastic temperature of 825 degrees C. The material characteristics obtained through multi-tube bulge test were compared to those obtained by tensile jump tests. The tube bulge forming was also simulated by finite element method (FEM) to verify the experimentally obtained material characteristics. Finally the results of estimated bulge time obtained from the simulations were compared to those of multi-tube bulge forming experiments. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: superplasticity; multi-tube bulge test; tubular material; strain rate sensitivity; finite element method; STRAIN-RATE SENSITIVITY; DOME FORMING TEST; DEFORMATION